Petanque Aceh Athletes Achievement From 2015 To 2020 - Abdurrahman*, Abdurrahman; Riski, Arpin; Ifwandi, Ifwandi; Zahara, Zahara; Sembiring, Ibrahim (Universitas Syiah Kuala, 2023)
Petanque is a sport that originates from France and is played using an iron ball, the aim of which is to bring the iron ball closer to the wooden ball. The aim of this research is to determine the achievements of Petanque Aceh athletes from 2015 to 2020. This research uses a historical descriptive method. The research subjects were 18 people consisting of the Chair of the Aceh FOPI Provincial Management, Aceh Petanque Coach, Petanque Sports Observer and Aceh Petanque Athletes. Data collection by interviews and documentation. Data analysis uses qualitative descriptive analysis. Based on research results, the achievements of the Aceh Petanque Team have developed very well so that they are able to achieve achievements from year to year, from 2017 to 2020 the Aceh Petanque Team has participated in 16 National Championships and 3 National Championships. International Championship, from the championship in which the Petanque Team participated in Aceh, a total of 57 medals were collected, divided into 22 gold medals, 14 silver medals and 21 bronze medals. The conclusion that can be seen is that the sporting achievements of Petanque Aceh are developing very well so that they are able to achieve brilliant achievements every year.